Role of intellectual and business workforce in building a knowledge-based and innovative society - Nguyen Viet Hoa (Journal SCIENCE AND TECHNOLOGY POLICIES AND MANAGEMENT, 2023)
The world is trending towards building a knowledge-based and innovative society in the context of the profound impact of the Fourth Industrial Revolution. Vietnam is actively participating in the Fourth Industrial Revolution, transforming the economic growth model from breadth to depth, and actively fulfilling international commitments to sustainable development. Therefore, intellectual and business workforces play a particularly important role in the cause of building and steadfastly protecting the socialist Fatherland of Vietnam as outlined by the Party in all Party Congresses until the 13th Congress. The theme "The role of intellectual and business workforces in a knowledge-based and innovative society," approaching social theory, Social Identity Theory (SIT), contributes to supplementing the theory of knowledge-based and innovative society, about intellectual and business workforces. Until now, there have not been many scientific works to approach the theoretical and practical system. The article focuses on two main issues: (1) The theory of intellectual and business workforces, knowledge-based society, and innovation; (2) The role of intellectual and business workforces in a knowledge-based and innovative society. Code: 23071401